What makes individual investors exercise early? Empirical evidence from the fixed-income market - Mathias Eickholt; Oliver Entrop; Marco Wilkens (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2014)
This paper studies the empirical early exercise behavior of Individual Investors in non-tradable putable bonds. Analyzing circa 31 million holding and exercise decisions of more than 220,000 Individual Investors over 13 years, our major findings are: (i) Individual Investors use their early exercise right predominantly at points in time that are not economically advisable, which results on average in negative excess returns from exercising. (ii) Only a small fraction of attractive exercise opportunities are exploited over time. (iii) Exercise behavior differs significantly among investor groups and is related to personal characteristics. (iv) The demand for liquidity and financial flexibility is apparently a more important investment and exercise motive than performance seeking.
Keywords: G10; G11; 650; early exercise; failure to exercise; liquidity demand; putable bond